Dialysis in crisis: Delivering renal replacement therapy in disasters, conflicts, and resource-constrained settings - Sourabh Sharma; Rasha Darwish; Sanjay Kalra; Sabine Karam (Journal of the Pakistan Medical Association, 2025)
Access to dialysis during crises such as natural disasters,armed conflicts, pandemics, or in low-resource settingsremains a significant global challenge. Vulnerablepopulations requiring chronic or acute dialysis aredisproportionately affected by disruptions ininfrastructure, supply chains, human resources, and wateror power availability. This article explores the operational,clinical, ethical, and logistical challenges faced whiledelivering dialysis in crisis scenarios. Drawing from globalcase studies including earthquakes in Japan, war zones inGaza, water-stressed regions, and lessons from theCOVID-19 pandemic, this paper highlights feasiblemodels of care, outlines adaptive strategies, and proposesa framework to improve dialysis delivery duringemergencies. Keywords: Crisis, Conflict, Dialysis, Disaster management,Emergency medicine, Humanitarian Health, PeritonealDialysis, Renal replacement therapy